DIURNAL TEMPERATURE RANGE VARIABILITY OVER KARNATAKA, INDIA: SPECTRAL EVIDENCE OF INTERANNUAL AND DECADAL CLIMATE MODES (1958–2024): DIURNAL TEMPERATURE RANGE VARIABILITY OVER KARNATAKA, INDIA - SRINIVASA SASDHAR PONNALURU (The Journal of Research ANGRAU, 2026)
Diurnal temperature range (DTR), defined as the difference between daily maximum and minimum temperatures, is an important indicator of climatic variability and land–atmosphere interactions. This study examines the temporal variability of DTR over Karnataka, India, using monthly temperature data for 1958–2024. Monthly DTR anomalies were analysed using Welch and Lomb–Scargle spectral techniques with statistical significance assessed against an AR(1) red-noise background. The results reveal variability across multiple timescales, including interannual (H=2–5 years), sub-decadal (H=8–9 years), and a statistically significant decadal cycle near 16–17 years. Additional low-frequency variability around 30 years indicates gradual climatic modulation of DTR. These findings highlight the presence of multi-timescale climate variability influencing diurnal temperature behaviour in southern India, with potential implications for agricultural planning and climate adaptation.